2013
DOI: 10.1007/s00018-013-1448-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term incubation with mifepristone (MLTI) increases the spine density in developing Purkinje cells: new insights into progesterone receptor mechanisms

Abstract: Cerebellar Purkinje cells (PC) physiologically reveal an age-dependent expression of progesterone with high endogenous concentrations during the neonatal period. Even if progesterone has been previously shown to induce spinogenesis, dendritogenesis and synaptogenesis in immature PC, data about the effects of progesterone on mature PC are missing, even though they could be of significant therapeutic interest. The current study demonstrates for the first time a progesterone effect, depending on the developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…Its exact mechanism of action is still unclear, but various studies have indicated an interaction with steroidogenesis (Hughes et al 2007;Brinton et al 2008;Rohe et al 2009). Indeed, current results strongly suggest that PGRMC1 directly interacts with the production of neurosteroids in Purkinje cells (Wessel et al 2014). Other research in different neuronal tissues revealed that increased PRGMC1 activation in response to progesterone leads to an increase in receptor expression.…”
Section: Pgrmc1 Induces Spinogenesis Even In Mature Purkinje Cellssupporting
confidence: 62%
See 4 more Smart Citations
“…Its exact mechanism of action is still unclear, but various studies have indicated an interaction with steroidogenesis (Hughes et al 2007;Brinton et al 2008;Rohe et al 2009). Indeed, current results strongly suggest that PGRMC1 directly interacts with the production of neurosteroids in Purkinje cells (Wessel et al 2014). Other research in different neuronal tissues revealed that increased PRGMC1 activation in response to progesterone leads to an increase in receptor expression.…”
Section: Pgrmc1 Induces Spinogenesis Even In Mature Purkinje Cellssupporting
confidence: 62%
“…Progesterone-induced up-regulation of PGRMC1 mRNA was observed after a spinal cord injury in rats (Labombarda et al 2003), whereas PGRMC1 expression was significantly lowered in the hypothalamic tissue of mice harboring a double knockout of progesterone receptor A and B (Krebs et al 2000). In the hippocampus, an increase in PGRMC1 was induced by cyclic progesterone exposure (Zhao et al 2012), and we, too, described a similar progesterone-dependent up-regulation of PGRMC1 in Purkinje cells (Wessel et al 2014). Not only did we observe an increase in PRGMC1 protein but also an increase in dendritic spine density when classical progesterone receptors were antagonized by mifepristone for more than 72 hours (mifepristone long-time incubation, MLTI) (Wessel et al 2014).…”
Section: Pgrmc1 Induces Spinogenesis Even In Mature Purkinje Cellsmentioning
confidence: 52%
See 3 more Smart Citations